2011
DOI: 10.1029/2011jc007121
|View full text |Cite
|
Sign up to set email alerts
|

Boundary mixing in lakes: 2. Combined effects of shear- and convectively induced turbulence on basin-scale mixing

Abstract: [1] A detailed comparison of results from a numerical three-dimensional hydrostatic lake model with high-resolution observations of the vertical structure of the turbulent bottom boundary layer (BBL) in a medium-size lake (Lake Alpnach, Switzerland) is provided. The focus of this study is on the shear-induced generation and destruction of stratification in the BBL that may ultimately lead to unstable layers (convection). The model was shown to provide a reliable description of the internal seiching dynamics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 37 publications
5
43
1
Order By: Relevance
“…Observations of shear-driven convection in lakes stem from two different single point observations in Lake Alpnach [17] and Lake Constance [4]. The results from these point measurements are consistent with analysis of numerical simulations of shear-driven convection [18], [19], [23]. Nonetheless, to date there are only a few field observations in lakes leaving it unclear as to the relative importance of shear-induced convection versus breaking of NLIW in energizing benthic BBLs.…”
Section: Introductionmentioning
confidence: 57%
“…Observations of shear-driven convection in lakes stem from two different single point observations in Lake Alpnach [17] and Lake Constance [4]. The results from these point measurements are consistent with analysis of numerical simulations of shear-driven convection [18], [19], [23]. Nonetheless, to date there are only a few field observations in lakes leaving it unclear as to the relative importance of shear-induced convection versus breaking of NLIW in energizing benthic BBLs.…”
Section: Introductionmentioning
confidence: 57%
“…Therefore, for diurnal forcing with s = (24 hours) À1 , small vertical wavelengths are favored in short (low L), strongly-stratified lakes. Previous observations show a tendency for short vertical wavelengths to be observed in small or medium lakes [LaZerte, 1980;Weigand and Chamberlain, 1987;Münnich et al, 1992;Vidal et al, 2005Vidal et al, , 2008Vidal and Casamitjana, 2007;Pannard et al, 2011;Lorrai et al, 2011].…”
Section: Discussionmentioning
confidence: 98%
“…Seiche dissipation generates turbulence, which is responsible for mixing heat [Lorrai et al, 2011], sediments [Pierson and Weyhenmeyer, 1994], chemicals [MacIntyre and Jellison, 2001], organisms [Serra et al, 2007], and pollutants [Sorensen et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown the effect of changing modes on the spatial variability of turbulence. Lorrai et al (2011) have shown how the mixing rates present variability at twice the seiching frequency. Sakai and Redekopp (2011) have also shown that, in a lake where super-inertial rotatory waves dominated, the superposition of higher modes enhanced particle transport.…”
Section: Vertical Structure Of the Internal Seichesmentioning
confidence: 96%
“…For this work, a 5-day spin-up period of the model was found to be enough for the standing waves to develop, although accurately settling the circulation of the lake might require a larger spin-up period (Korotenko et al, 2010). Lorrai et al (2011) also used a spin-up period of 5 days of the 3-D hydrostatic Boussinesq model to study the seiching dynamics of a medium-size lake. Note that if the POM model had not reproduced the modes studied in this paper, the surface elevation filtered around the periods of the observed oscillations would not present a coherent structure over the lake that is repeated for every period, as presented in the results section.…”
Section: Numerical Simulationsmentioning
confidence: 99%